Arthropods and Fire Within the Biologically Diverse Longleaf Pine Ecosystem. (24th November 2021) - Sheehan, Thomas N; Klepzig, Kier D
Abstract: The longleaf pine Pinus palustris Miller (Pinales: Pinaceae) ecosystem once covered as many as 37 million hectares across the southeastern United States. Through fire suppression, development, and conversion to other plantation pines, this coverage has dwindled to fewer than 2 million hectares. A recent focus on the restoration of this ecosystem has revealed its complex and biologically diverse nature. Arthropods of the longleaf pine ecosystem are incredibly numerous and diverse—functionally and taxonomically. To provide clarity on what is known about the species and their functional roles in longleaf pine forests, we thoroughly searched the literature and found nearly 500 references. In the end, we tabulated 51 orders 477 families, 1, 949 genera, and 3, 032 arthropod species as having been stated in the scientific literature to occur in longleaf pine ecosystems. The body of research we drew from is rich and varied but far from comprehensive. Most work deals with land management objective associated taxa such as pests of pine, pests of—and food for—wildlife (red-cockaded woodpecker, northern bobwhite quail, gopher tortoise, pocket gopher, etc.), and pollinators of the diverse plant understory associated with longleaf pine. We explored the complex role frequent fire (critical in longleaf pine management) plays in determining the arthropod community in longleaf pine, including its importance to rare and threatened species. We examined known patterns of abundance and occurrence of key functional groups of longleaf pine-associated arthropods. Finally, we identified some critical gaps in knowledge and provide suggestions for future research into this incredibly diverse ecosystem.